Comparison of atmosphere/aquatic environment concentration ratio of volatile chlorinated hydrocarbons between temperate regions and Antarctica - ZOCCOLILLO, Lelio; INSOGNA, SUSANNA; Luca Amendola (Chemosphere, 2009)
For the purpose of understanding the transport and deposition mechanisms and the air-water distribution of some volatile chlorinated hydrocarbons (VCHCs), their atmosphere/aquatic environment concentration ratio was evaluated. In addition, for the purpose of differentiating VCHC behaviour in a temperate climate from its behaviour in a polar climate, the atmosphere/aquatic environment concentration ratio evaluated in matrices from temperate zones was compared with the concentration ratio evaluated in Antarctic matrices. In order to perform air samplings also at rigid Antarctic temperatures, the sampling apparatus, consisting of a diaphragm pump and canisters, was suitably modified. Chloroform, 1,1,1-trichloroethane, tetrachloromethane, 1,1,2-trichloroethylene and tetrachloroethylene were measured in air, water and snow using specific techniques composed of a purpose-made cryofocusing-trap-injector (for air samples) and a modified purge-and-trap injector (for aqueous samples) coupled to a gas chromatograph with mass spectrometric detection operating in selected ion monitoring mode. The VCHCs were retrieved in all the investigated matrices, both Italian and Antarctic, with concentrations varying from tens to thousands of ng m(-3) in air and from digits to hundreds of ng kg(-1) in water and snow. The atmosphere/aquatic environment concentration ratios were always found to be lower than 1. In particular, the Italian air/water concentration ratios were smaller than the Antarctic ones, by reason of the higher atmospheric photochemical activity in temperate zones. On the other hand, the Antarctic air/snow concentration ratios proved to be largely in favour of snow with respect to the Italian ratios, thus corroborating the hypothesis of a more efficient VCHC deposition mechanism and accumulation on Antarctic snow. (C) 2009 Elsevier Ltd. All rights reserved.